Dialectic approach for using viewpoint discrepancies in learning - Panayiotou, Christiana; Dimitrova, Vania G. (My University, 2007)
The paper proposes a dialectic approach to exploit discrepancies of viewpoints for learning. The approach is illustrated with an elaborated example. A computational framework of a pedagogical agent capable of interacting with a learner for discussing different viewpoints in the same domain is outlined. The framework employs AI technologies, such as argumentation for defeasible reasoning, situation calculus for contextualized reasoning and dialogue management. The approach can be applied in interactive learning environments to promote awareness, reflection, and conceptual change.
Keywords: Argumentation; Conceptual discrepancies; Context; E-learning; Viewpoints